Challenges and Opportunities of Green Innovation for Indonesian MSMEs: Integrating Maqasid Shariah Perspective with 2024 KADIN Data - Yunus, Asmar; arif, Adriansyah; Yunita Yusuf, Yulia; Gaffar, Andi Nurrahma; Syukur, Mukarramah (PINISI Discretion Review, 2025)
The transformation towards a green economy presents a strategic challenge and opportunity for Indonesian MSMEs (Micro, Small, and Medium Enterprises), which comprise over 99% of national business units. This descriptive-qualitative documentary study, utilizing secondary data from KADIN, BPS, and the Ministry of Cooperatives and SMEs, aimed to analyze the challenges and opportunities for implementing Green Innovation in MSMEs, based on 2024 data from KADIN Indonesia, and to review its relevance through the perspective of maqashid syariah (the objectives of Sharia). The findings reveal that green adoption is hindered by low technology literacy, limited access to green financing, inadequate HR training, and insufficient halal and environmental certification, yet significant opportunities exist due to rising consumer awareness of eco-friendly and halal products, supportive green financing policies from the OJK, and free halal certification programs from BPJPH. From a maqashid syariah perspective, Green Innovation aligns with the spiritual and moral objectives of Hifz al-Din (preservation of religion) and Hifz al-Nafs (preservation of life), underscoring ethical halal production, environmental sustainability, and social responsibility. The study concludes that the synergy between Green Innovation and Islamic values can enhance MSME competitiveness and foster an inclusive, equitable, and sustainable green and halal economic ecosystem in Indonesia.